2000
DOI: 10.1130/0091-7613(2000)28<3:cviteu>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Climatic variability in the eastern United States over the past millennium from Chesapeake Bay sediments

Abstract: anthropogenic perturbations to Earth's atmosphere, or a combination of factors (Rind and Overpeck, 1993). Because instrumental records rarely exceed 100 yr, paleoclimate reconstructions can establish which factors are most important over multidecadal time scales, distinguish anthropogenic and natural causes, and test climate-model simulations of decadal-and centennial-scale variability (Latif, 1998). Paleoclimatic records from polar and tropical regions suggest that decadal-and centennial-scale climate changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 32 publications
3
53
0
Order By: Relevance
“…Also, the d 18 O variations at White Lake are consistent with the paleosalinity reconstructed from Chesapeake Bay over the last ∌240 years [Cronin et al, 2000], with higher d 18 O values at White Lake corresponding to higher salinities at Chesapeake Bay (Figures 2b and 2c). Paleosalinity was reconstructed using a quantitative relationship between the salinity and relative abundance of the benthic foraminifer Elphidium [Cronin et al, 2000]. Changes in paleosalinity at Chesapeake Bay reflect changes in precipitation in the watershed and fresh-water discharge to the Bay [Cronin et al, 2000].…”
Section: Proxy Records Of Multidecadal Moisture Variationssupporting
confidence: 75%
See 1 more Smart Citation
“…Also, the d 18 O variations at White Lake are consistent with the paleosalinity reconstructed from Chesapeake Bay over the last ∌240 years [Cronin et al, 2000], with higher d 18 O values at White Lake corresponding to higher salinities at Chesapeake Bay (Figures 2b and 2c). Paleosalinity was reconstructed using a quantitative relationship between the salinity and relative abundance of the benthic foraminifer Elphidium [Cronin et al, 2000]. Changes in paleosalinity at Chesapeake Bay reflect changes in precipitation in the watershed and fresh-water discharge to the Bay [Cronin et al, 2000].…”
Section: Proxy Records Of Multidecadal Moisture Variationssupporting
confidence: 75%
“…However, the available instrumental data for the Mid-Atlantic region are either incomplete or inconsistent with each other, making it difficult to further test these ideas for a longer time-frame. Extending the instrumental record to longer time periods requires high-resolution paleoclimate reconstructions, and surprisingly very few high-resolution paleoclimate records [e.g., Cronin et al, 2000] are available for the highly populated Mid-Atlantic region.…”
Section: Introductionmentioning
confidence: 99%
“…This exercise would be meaningful in the sense that all estuaries may be affected by climate change, particularly through river runoff changes (Miller and Russell 1992). Likewise, the modeling scheme developed here is easily adaptable for reverse calculations, such as reconstructing ancient watershed hydrology and climate using fossil proxies as salinity inputs (Cronin et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…While most recent drought research has taken place in the western half of the United States (where extended drought is more likely due to high interannual variability in precipitation; Diaz 1983), a few investigators have studied multidecadal drought in the eastern United States. Cronin et al (2000Cronin et al ( , 2005, for example, found evidence of drought variability in Chesapeake Bay sediments over the past several millennia. More recently, they identified 14 dry/wet cycles since 1500 AD and found evidence of multidecadal droughts in the 16th and 17th centuries.…”
Section: Proxy Recordmentioning
confidence: 99%